Enviromental influence on the expression of wheat protein fractions under South African drylands conditions - Wentzel, Barend Smit (University of the Free State, 2017)
Ten South African hard red wheat cultivars (BettaDN, Caledon, Elands, Gariep, Komati, Limpopo, Matlabas, PAN3118, PAN3349 and PAN3377) were planted at five localities over two seasons in the winter dryland wheat production area of South Africa. Localities were divided into North Western Free State (NW-FS) and Eastern Free State (E-FS). Size-exclusion high-performance liquid-chromatography was applied to determine the molecular weight distribution of SDS-extractable protein and SDS-unextractable protein fractions. Relative and absolute amounts were measured for glutenin, gliadin, albumin and globulin. Protein fractions did not increase parallel to increased flour protein content. The gliadin fraction showed the highest correlation in NW-FS, while polymeric proteins showed the highest correlation in E-FS with flour protein content. Albumin and globulin showed the lowest correlation with flour protein content in both regions. Environment made the largest contribution to variation in flour protein content in both regions. Bread making properties were correlated with flour protein content and protein fractions. Significant positive correlations were observed between flour protein content and wet gluten content, farinograph water absorption, alveograph extensibility, alveograph strength and loaf volume. Significant negative correlations occurred between flour protein content and SDS-sedimentation and alveograph tenacity. Mixograph peak time was mainly influenced by genotype and did not correlate significantly with flour protein content, while unextractable polymeric proteins showed a significant positive correlation with mixograph peak time. Partial correlations were conducted to remove the quantitative effect of flour protein content. Polymeric and monomeric protein fractions affected bread making quality differently in NW-FS than E-FS, indicating the effect of environment on protein composition. Pearson’s correlation showed that flour protein content correlated between significantly and not significantly with alveograph tenacity, alveograph extensibility and mixogrpah peak time MPT for individual cultivars. The stepwise multiple linear regression indicated that flour protein content could only explain variation in alveograph extensibility and loaf volume for two cultivars in E-FS. Protein fractions contributed in different degrees to variation for alveograph tenacity, alveograph extensibility, mixograph peak time and loaf volume for individual cultivars and between the two regions. The model explained a larger percentage of variation in alveograph extensibility for BettaDN, Caledon, Elands, Gariep, Komati and Limpopo in E-FS than in NW-FS, while the model explained a larger proportion of variation in mixograph peak time for Matlabas and the Pannar cultivars in NW-FS than in E-FS. Albumin and globulin fractions contributed more to variation for alveograph tenacity, alveograph extensibility and mixograph peak time in NW-FS than in E-FS. The effect of albumin and globulin on baking quality justifies further research. Environment had a large influence on flour protein content and percentages of protein fractions. Protein fractions affected baking quality differently between environments and genotypes.

Tien Suid Afrikaanse harde rooi koringkultivars (BettaDN, Caledon, Elands, Gariep, Komati, Limpopo, Matlabas, PAN3118, PAN3349 en PAN3377) is aangeplant oor vyf lokaliteite en twee seisoene, in die winter droëland koringproduksie streek van Suid Afrika. Lokaliteite was verdeel in Noordwes-Vrystaat (NW-VS) en Oos-Vrystaat (O-VS). Molekulêre gewig verspreiding van SDS-oplosbare en SDS-nie-oplosbare proteïenfraksies is bepaal met hoë uitset vloeistofchromatografie. Relatiewe en absolute hoeveelhede is bepaal vir glutenien, gliadien, albumien en globulien. Proteïenfraksies het nie parallel met meel proteïeninhoud vermeerder nie. Gliadiene het die hoogste korrelasie met meel proteïeninhoud getoon in NW-VS, terwyl polimeriese proteïene die hoogste korrelasie getoon het in O-VS. Albumien en globulien het die laagste korrelasie getoon met meel proteïeninhoud. Omgewing het die grootste bydrae gemaak tot variasie in meel proteïeninhoud in beide streke. Korrelasies is bepaal tussen meel proteïeninhoud en proteïenfraksies met bakkwaliteit eienskappe. Betekenisvolle positiewe korrelasies is waargeneem tussen meel proteïeninhoud en nat gluten inhoud, farinograaf waterabsorpsie, alveograaf rekbaarheid, alveograaf sterkte en broodvolume. Betekenisvolle negatiewe korrelasies het voorgekom tussen meel proteïeninhoud en SDS-sedimentasie en alveograaf weerstand teen uitrekking. Miksograaf mengtyd was hoofsaaklik deur die genotipe beïnvloed en het nie ‘n betekenisvolle korrelasie met meel proteïeninhoud getoon nie, terwyl nie-oplosbare polimeriese proteïene ‘n betekenisvolle positiewe korrelasie met miksograaf mengtyd getoon het. Gedeeltelike korrelasies is ook uitgevoer, waar die kwantitatiewe effek van meel proteïeninhoud verwyder word. Polimeriese en monomeriese proteïenfraksies beïnvloed kwaliteitseienskappe verskillend in NW-VS teenoor die O-VS, wat dui op die invloed van die omgewing op proteïensamestelling. Meel proteïeninhoud vir individuele kultivars se korrelasies het gewissel tussen betekenisvol en nie-betekenisvol met alveograaf weerstand teen uitrekking, alveograaf rekbaarheid en miksograaf mengtyd. Stapsgewyse veelvuldige liniêre regressie het aangedui dat meel proteïeninhoud alleen, variasie in alveograaf rekbaarheid en broodvolume slegs vir twee kultivars in O-VS kon verklaar. Proteïenfraksies het verskillend bygedra tot variasie in alveograaf weerstand tot uitrekking, miksograaf mengtyd en broodvolume vir individuele kultivars en tussen die twee streke. Die model kon ‘n groter persentasie van variasie verklaar in alveograaf rekbaarheid vir BettaDN, Caledon, Elands, Gariep, Komati en Limpopo in O-VS teenoor NW-VS, terwyl die model ‘n groter persentasie van variasie in miksograaf mengtyd in Matlabas en die Pannar kultivars verklaar in NW-VS teenoor O-VS. Albumien en globulien fraksies het ‘n groter bydrae gemaak tot variasie in alveograaf weerstand tot uitrekking, alveograaf rekbaarheid en miksograaf mengtyd in NW-VS teenoor O-VS. Die effek van albumien en globulien op eienskappe vir bakkwaliteit regverdig verdere navorsing. Omgewing het ‘n groot invloed op meel proteïeninhoud en hoeveelhede van proteïenfraksies gehad. Die invloed van proteïenfraksies op eienskappe vir bakkwaliteit het verskil tussen genotipes en omgewings. Verskillende genotipes en omgewings mag verskillende resultate oplewer.
Thesis (Ph.D. (Plant Sciences))--University of the Free State, 2017
Keywords: Hard red wheat cultivars; Environment; Molecular weight distribution; Flour protein content; Protein fractions; Baking quality; Stepwise multiple linear regression; Wheat -- South Africa